IMPULSE CONTROL OF THE MANIPULATION ROBOT - Yurii F. Dolgii; Alexander N. Sesekin; Ilya G. Chupin (Ural Mathematical Journal, 2019)
A nonlinear control problem for a manipulation robot is considered. The solvability conditions for the problem are obtained in the class of special impulse controls. To achieve the control goal, the kinetic energy of the manipulation robot is used. When finding analytical formulas for controls, the classical first integrals of Lagrangian mechanics were used. The effectiveness of the proposed algorithm is illustrated by computer simulation.